Hyperalgesic Activity of Kisspeptin in Mice. Issue 1 (23rd November 2011) - Spampinato, Simona; Trabucco, Angela; Biasiotta, Antonella; Biagioni, Francesca; Cruccu, Giorgio; Copani, Agata; Colledge, William H; Sortino, Maria Angela; Nicoletti, Ferdinando; Chiechio, Santina
Background: Kisspeptin is a neuropeptide known for its role in the hypothalamic regulation of the reproductive axis. Following the recent description of kisspeptin and its 7-TM receptor, GPR54, in the dorsal root ganglia and dorsal horns of the spinal cord, we examined the role of kisspeptin in the regulation of pain sensitivity in mice. Results: Immunofluorescent staining in the mouse skin showed the presence of GPR54 receptors in PGP9.5-positive sensory fibers. Intraplantar injection of kisspeptin (1 or 3 nmol/5 μl) induced a small nocifensive response in naive mice, and lowered thermal pain threshold in the hot plate test. Both intraplantar and intrathecal (0.5 or 1 nmol/3 μl) injection of kisspeptin caused hyperalgesia in the first and second phases of the formalin test, whereas the GPR54 antagonist, p234 (0.1 or 1 nmol), caused a robust analgesia. Intraplantar injection of kisspeptin combined with formalin enhanced TRPV1 phosphorylation at Ser800 at the injection site, and increased ERK1/2 phosphorylation in the ipsilateral dorsal horn as compared to naive mice and mice treated with formalin alone. Conclusion: These data demonstrate for the first time that kisspeptin regulates pain sensitivity in rodents and suggest that peripheral GPR54 receptors could be targeted by novel drugs in the treatment of inflammatory pain.